Proposed new interior design of Junk Bookstore at No 51 Jalan Plumbum P 7/P, Seksyen 7, 40000, Shah Alam, Selangor Darul Ehsan for Permaijana Setia (M) Sdn Bhd / Nur Anis Amalina Mohamad Azmi - Mohamad Azmi, Nur Anis Amalina (2012)
The requirements of a Final Student of Diploma in Interior Architecture is to come out with a new project report and proposal regarding interior design project. This is to understand the process of design field from the smallest scope of detailing to the final presentation. The project proposal title is Proposed New Interior Design Scheme of Junk Bookstore at No 51Jalan Plumbum P 7/P Seksyen 7 ,40000 Shah Alam Selangor Darul Ehsan for Permaliana Setia (M) Sdn Bhd. Junk Book Store is a secondhand book store . It was first opened for business on 2nd May 1990 in a small room with a space of only 600 sq. ft. on the first floor at Wisma Ann Koai, Jalan Ampang, Kuala Lumpur. Though small in size, the store offers an extensive range of general books, magazines and comics. Mr. Tan and Adelyn Koh , the owner, had to opt for another bigger shop where a three-storey pre-war shoplot, between breaths of carbon monoxide from the perpetually buzzing Jalan Tun H. S. Lee at No. 78 came to be on January 28, 1996. 1998 saw the big triumph as Junk Book Store was awarded "The Biggest Secondhand Bookstore" by the Malaysia Book of Records, first-of-its-kind. The bookstore is full with treasure trove of out-of-print, rare first edition, hard to find quality books on all subjects (Malaya History, Malaya Published Books, History of all countries, World War II, Biographies, etc., old LP records, magazines and Marvel comics) from the 17th to the 20th century. The whole ambience of Junk Book Store looks like an old library well stocked with an impressive inventory of books, magazines, Marvel Comics and LP records. There is also a section of foreign languages books where backpackers read and enjoy. This design project proposal and research are based on client's requirements, intention, demand , and also based on the company's mission and vision. The main objective of this design project and research is to design a new scheme of a secondhand book store, according to client's intention and requirements which is to apply sustainable and green issue on the design of the interiors along with its original concept of a green concept bookstore. Besides, the Junk Bookstore also has an intention to propose a new corporate identity suitable with its concept of the awareness of global issue. This project is a a project where stages and process of research , building study, design exploration , space planning and analysis of client demand and requirements are being held.